Bahasa Indonesia - Hutauruk, Agnes Vania; Siladharma, IGB; Dirgayusa, IGN Putra; Hakiki, Irham Adrie (Journal of Marine Research and Technology; Vol 8 No 1 (2025): FEBRUARI 2025DO - 10.24843/JMRT.2025.v08.i01.p03, 2025)
There is a possibility that the shoreline will change annually. Shoreline changes can be influenced by factors such as waves, currents, wind, tides, and sediment transport. This can lead to erosion and accretion. The area around the Tukad Unda Estuary (from Jumpai Beach to Gunaksa Harbor) is prone to coastal accretion. This study employs the MIKE 21 software and a numerical model method, specifically a one-line model for only one year from 2018 to 2019, to analyze shoreline changes. A sensitivity analysis was also run on six scenarios. Each scenario had a different active depth value to see its effect on shoreline changes and get results close to the coastline in 2019. The basic scenario's active depth is 5 while scenario I's is 75, scenario II's is 185, scenario III's is 279, scenario IV's is 750, and scenario V's is an interpolated number between 75 and 750. The basic scenario simulated with an active depth value of 5 showed an extremely distinct shift in the shoreline from 2019. Following multiple scenario simulations, it was discovered that the result of shoreline changes from scenario V was close to the coastline in 2019. Scenario V reveals both accretion and erosion, but accretion dominates.